Introduction [in Future directions for Indian irrigation: research and policy issues] - Svendsen, Mark (International Food Policy Research Institute, 1990)
This set of chapters resulted from a workshop organized by the International Food Policy Research Institute (IFPRI) and held in April 1988 in Ootacamund, Tamil Nadu, India. The workshop was hosted by Tamil Nadu Agricultural University, Coimbatore, and was designed to review critical strategic problems facing the irrigation sector in India. The larger aim of the meeting was to assist in developing an agenda of research issues to receive attention as part of the recently initiated program of collaborative agricultural policy research being undertaken by IFPRI and selected Indian research institutions.